An Imaging HF GPR Using Stationary Antennas: Experimental Validation Over the Antarctic Ice Sheet - Le Gall, Alice; Ciarletti, Valérie; Berthelier, Jean-Jacques; Reineix, Alain; Guiffaut, Christophe; Ney, Richard; Dolon, F.; Bonaime, Sébastien (IEEE Transactions on Geoscience and Remote Sensing, 2008)
International audience Terrestrial And Planetary Imaging Radar (TAPIR) is an innovative high-frequency ground-penetrating radar (GPR) developed in the frame of the Martian NetLander mission to probe the subsurface down to kilometric depths. Unlike most GPRs, TAPIR is able to image underground reflectors with stationary antennas. In this paper, after a brief presentation of the instrument, we describe the method developed to interpret data collected during the RAdar of NEtlander in Terre Ade acutelie (RANETA) field survey in Antarctica. This method consists of retrieving the direction of arrival of each detected echo through the measurement of five components of the electromagnetic field (the three magnetic components and the horizontal components of the electric field). Thus, both the range and the direction of each individual reflection or diffraction due to the ice-bedrock interface are resolved. We validated this method on finite-difference time-domain numerically simulated data for different subsurface configurations before applying it to RANETA observations. In particular, the irregular topography of the bedrock in two sounding sites was revealed. We discuss the accuracy of our results